A scientific approach to improve physiological capacity of an elite cyclist - Rønnestad, B. R.; Hansen, J. (International Journal of Sports Physiology and Performance, 2018)
Previous studies in endurance athletes have indicated that block periodization (BP) can be a good alternative to the more traditional organization of training despite the fact that the total volume and intensity of the training are similar. However, these studies usually last only 4-12 wk. The aim of the present single-case study was to investigate the consequences of 58 wk with systematic BP of low-intensity training (LIT), moderate-intensity training (MIT), and high-intensity interval training (HIT) including incorporation of heavy strength training. It is important that a maintenance stimulus on the nonprioritized training modalities was added in the different training blocks. Performance-related variables were tested regularly during the intervention. The studied cyclist started with a maximal oxygen uptake (VO2max) of 73.8 mL/kg·min, peak aerobic power (Wmax) of 6.14 W/kg, and a power output at 3 mmol/L blood lactate concentration (Power3la-) of 3.6 W/kg. Total training volume during the 58-wk intervention was 678 h, of which 452 h were LIT (67%), 124 h were MIT (18%), 69 h were HIT (10%), and 34 h were heavy strength training (5%). The weekly training volume had a large range depending on the focus of the training block. After the intervention the cyclist`s VO2max was 87 mL/kg·min, Wmax was 7.35 W/kg, and Power3la- was 4.9 W/kg. This single case indicates that the present training program can be a good alternative to the more traditional organization of long-term training of endurance athletes. However, a general recommendation cannot be given based on this single-case study.